Panel products from Melia dubia - Vijay Kumar, Prakash; Singh, M.P.; Sujatha, D.; Uday, D.N.; Mamatha, B.S.; Kiran, M.C.; Narasimhamurthy, (Indian Forester, 2022)
The demand and supply gap for wood is showing an ever increasing trend and in order to counter act on this trend, efforts are made in all possible ways to substitute wood with suitable alternatives wherever possible and to shift the focus from natural forests to private plantations for sourcing the timber raw material for wood based industries. As part of this efforts, local timbers are being extensively studied for their suitability for producing wood based composites which could replace the solid wood without compromising in either aesthetic appearance or strength properties. Clones of Eucalyptus, Poplar, Silver oak etc. are a few timber species to name. Melia dubia is one such plantation timber suitable for farm forestry and agro forestry which is becoming trendy among present day farmers, private planters and wood based industries because of its fast growth, inherited anti-termite and anti-insect properties etc. This paper presents the research results of a series of studies conducted to find the suitability of Melia dubia for manufacturing Particleboard, Medium density fiberboards (MDF), Laminated Veneer Lumber (LVL) and Blockboard.Â 